Results from one and two implants compared with yearling cattle on summer pasture - R. Pruitt; A. Fleck; E.F. Smith; L. Corah; Clenton E. Owensby (Kansas Agricultural Experiment Station Research Reports, 1978)
Reimplanting Ralgro in mid-July after implanting in late April did not improve daily summer gains compared to a single implant.
Keywords: Cattlemen' s Day; 1978; Report of progress (Kansas State University. Agricultural Experiment Station); 320; Beef; Implants; Yearling cattle